Assessment of Contingent Liabilities and Their Impact on Debt Dynamics in South Africa - Bachmair, Fritz Florian; Bogoev, Jane (World Bank, Washington, DC, 2018)
The aim of this analysis is to quantify the losses from potential materialization of contingent liabilities by applying a new methodology for the case of South Africa and, to assess their impact on debt dynamics. Accordingly, we bring a novelty to this research by utilizing probabilities of distress, which is a different approach compared to the existing, already applied methodology. The central finding of the simulations conducted is that estimated losses from contingent liabilities, are significantly lower in the first year when they materialize compared to the existing applied methodology, and will gradually add up over time. Accordingly, the solvency and liquidity situation in the country will deteriorate. For example, the largest deterioration will occur in the debt to GDP ratio where the debt accumulation may be higher by 2.1 percent of GDP within three years, compared to the baseline projection. What is more concerning is that the debt trajectory is not stabilizing and losses incurred from materialization of contingent liabilities may become significant driving factor of debt accumulation in medium-term. Ultimately, the current estimates suggest that contingent liabilities may constitute a drag to fiscal policy in medium-term and their long-term accumulation may jeopardize the debt sustainability of the country. In that respect, this analysis suggests remedial measures and building protective buffers by the South African Treasury in the case CLs materialize.